(untitled) (Ameghiniana, 2014)
Spore groups recovered from Miocene samples from the Chiquimil Formation, Vallecito,Ca tamarca Province, Argentina, are presented. On the basis of their taxonomy and chronostratigraphic range, it was possible to distinguish: 1) Miocene autochtonous species: Laevigatosporites ouatus Wilson and Webster, Rugulatisporites caperaius Hoeken-Klinkenberg, Stereisporites antiquasporites (Wilson and Webster) Dettmann, Polypodiaceoisporites iumuiaius Partridge, Reticuloidosporites tenellis Krutzsch, Leiotriletes regularis (Pflug) Krutzsch, Gleiclzeniidites senonicus Ross, Todisporites majar Couper, Cyathidites minar Couper, Todisporites niinor Couper, Dictyophylidites mortoni (jersey) Playford and Dettmann, Díctyophylidites arcuaius Pocknall and Mildenhall, Osmundacidites ciliatus Sah, Cyathídítes congoensís Sah, Polypodiaceoisporites simplex Sah, Baculatisporites comaumensis (Cookson) Potonié, Polypodiisporites speciosus (Harris) Khan and Martín, Tuberculatosporites parous Archangelsky, Deltoidospora minar (Couper) Pocock; among them the following taxa are recorded for the first time in the Cainozoic of Argentina: Dictyophyllidites arcuaius Pocknall and Mindelhall, Cyathidites congoensis Sah, Rugulatisporites caperaius Hocken-Klinkenberg, Verrucingulatisporites sp., Undulatisporites sp.) Mesozoic reworked species: Plicifera delicata Bolchovitina, Biretisporítes potoniaei (Delcourt and Sprumont) Delcourt et al.; Biretisporites sp. A Archangelsky and Seoane, Reticulatisporiies sp. Baldoni and Archangelsky, Leptolepidites majar Couper, Annulispora folliculosa (Rogalska) de Jerseyand Fooeotriletes micrcfoueotatus Menéndez. Systematic descriptions of spores unidentified at specific level